Effect of free thymol on differential gene expression in gastric mucosa of the young pig. (20th February 2014) - Colombo, M.; Priori, D.; Gandolfi, G.; Boatto, G.; Nieddu, M.; Bosi, P.; Trevisi, P.
Abstract : Thymol is the most common molecule in thyme and has been proposed as an oral alternative to antibiotics in the feed of pigs and broilers. The knowledge of the in vivo physiological effects of thymol on tissues is limited, particularly its impact on the gastric mucosa, where it is primarily absorbed when it is orally supplied. In this study, thymol (TH, 50 mg/ kg BW) or a placebo (CO) was introduced directly into the stomach of 8 weaned pigs that were slaughtered 12 h later and sampled for gastric oxyntic and pyloric mucosa. The analysis of whole transcript expression was performed using Affymetrix © Porcine Gene 1.1 ST array strips. Affymetrix Transcripts IDs were associated with 13 406 human gene names based on Sus scrofa Ensemble. Gene Set Enrichment Analysis was performed, comparing TH and CO pigs. For each gene set, the normalized enrichment score (NES) was defined as significant when the false discovery rate % was <25 and the P -value of NES was <0.05. In response to TH, 72 and 19 gene sets were significantly enriched in the oxyntic and pyloric mucosa, respectively. Several gene sets involved in mitosis and its regulation ranked near the top, primarily in the oxyntic mucosa; the gene set DIGESTION ranked first and ninth in the pyloric and oxyntic mucosa, respectively. Within this group, somatostatin (SST), SST receptors, peptide transporter 1 (SLC15A1) and calpain 9 (gastrointestinal tract-specific calpain) were the most strongly upregulated genes. Thymol reduced the enrichment of 120 and 59 gene sets in the oxyntic and pyloric mucosa, respectively. Several gene sets related to ion transport and channeling and aqueous pores across membranes, including short transient receptor potential (TRP) channel 4, potassium voltage-gated channel members 1 and 2, and ryanodine receptors 2 and 3, were less enriched. The downregulation of these genes sensitive to thymol in vitro could depend on the thymol dose and contact with the gastric tissues that causes an adaptive response with their reduced activation. Conversely, the activation of the TRPA1 gene (ranked 1072 and 128 among all the genes in the oxyntic and pyloric mucosa, respectively) indicates the involvement of another TRP-regulating cellular calcium storage. In conclusion, the stimulation of gastric proliferative activity and the control of digestive activity by thymol can influence positively gastric maturation and function in the weaned pigs. These properties should be considered in addition to thymol's antimicrobial properties when supplementation of this molecule in feed is evaluated.